Beyond Traditional Security: Leveraging Emerging Technologies for Cyber Resilience - Madhi, Ahmad Ehab (2025)
This work proposes a multi-layered cybersecurity framework that integrates Artificial Intelligence (AI), quantum-safe cryptography, and blockchain to address the limitations of traditional security systems. AI plays a central role by enabling real-time threat detection, predictive analytics, and automated response through machine learning and deep learning models. The framework aims to proactively protect critical infrastructure and adapt to AI-driven attack vectors, which are increasingly sophisticated and dynamic. By